TAX AVOIDANCE AND DERIVATIVES' EFFECT ON FIRM VALUE MODERATED WITH OWNERSHIP CONCENTRATION AND AFFILIATED RELATIONSHIP - Rani, Imelda; Imelda, Elsa; Magdalena, Fanny (International Journal of Application on Economics and Business, 2024)
The purpose of this study is to examine the impact of tax avoidance and derivatives on firm value, as well as the role of ownership concentration and affiliate ties in modulating the relationship between tax avoidance and firm value. All energy sector businesses listed on the Indonesia Stock Exchange make up the study's population, which will be examined between 2020 and 2022. The sample for this study, which was conducted during the same time period, consisted of 44 energy-related enterprises. The data processing for this study included Eviews 13 software, as well as multiple linear regression and Moderated Regression Analysis methods. The results of the study show that ownership concentration significantly and positively raises firm value. However, derivatives and tax avoidance have no significant effect on it. Ownership concentration and affiliation is proven fail to strengthen the relationship between tax avoidance and firm value. According to this study, investors consider the level of concentrated ownership when making investment decisions. This means that the company's key shareholders must perform their duties to the best of their abilities in order for the company to develop and maintain strong future prospects.